Juggling two pandemics: The simultaneous necessity and difficulty of practising lifestyle medicine during the COVID‐19 era. Issue 3 (3rd August 2022) - Shipley, Alexandra; Fallows, Ellen
Abstract: Since early 2020, COVID‐19 has dominated headlines, claimed millions of lives, crippled global economies, overwhelmed health services, attracted multi‐disciplinary scientific attention and transformed our daily lives. Unsurprisingly, the Lifestyle Medicine field has not been immune to the pandemic's wide‐reaching influence. Although COVID‐19 highlighted the necessity of maintaining healthy behaviours, the associated lockdowns and social distancing measures challenged our ability to do so. Attempts to mitigate the spread of COVID‐19 may, therefore, have exacerbated the obesity pandemic and other diseases associated with unhealthy lifestyle habits. One hopes this devastating virus provides the impetus for policymakers, clinicians and patients to collaborate in tackling the diseases of modern life. This commentary explores how lifestyle‐correlated conditions (which are closely intertwined with socioeconomic factors) rendered much of the UK population vulnerable to COVID‐19 infection, morbidity and mortality. Subsequently, we consider the impact of lockdown measures on the accessibility of healthy living, focussing on eating behaviours, physical activity, relationships, sleep and substance abuse, as well as the social demographics particularly affected. Approaching the aftermath of this vicious cycle with optimism, we discuss why the post‐Covid era presents a unique opportunity for Lifestyle Medicine, as an evidence‐based approach to supporting patients to adopt and sustain healthy behaviours.